Global DNA methylation and cognitive and behavioral outcomes at 4 years of age: A cross‐sectional study. Issue 4 (28th February 2020) - Taylor, Rachael M.; Smith, Roger; Collins, Clare E.; Mossman, David; Wong‐Brown, Michelle W.; Chan, Eng‐Cheng; Evans, Tiffany‐Jane; Attia, John R.; Buckley, Nick; Drysdale, Karen; Smith, Tenele; Butler, Trent; et al.
Abstract: Background: Accumulating evidence suggests that breastfeeding exclusivity and duration are positively associated with child cognition. This study investigated whether DNA methylation, an epigenetic mechanism modified by nutrient intake, may contribute to the link between breastfeeding and child cognition. The aim was to quantify the relationship between global DNA methylation and cognition and behavior at 4 years of age. Methods: Child behavior and cognition were measured at age 4 years using the Wechsler Preschool and Primary Scale of Intelligence, third version (WPPSI‐III), and Child Behavior Checklist (CBC). Global DNA methylation (%5‐methylcytosines (%5mC)) was measured in buccal cells at age 4 years, using an enzyme‐linked immunosorbent assay (ELISA) commercial kit. Linear regression models were used to quantify the statistical relationships. Results: Data were collected from 73 children recruited from the Women and Their Children's Health (WATCH) study. No statistically significant associations were found between global DNA methylation levels and child cognition or behavior ( p > .05), though the estimates of effect were consistently negative. Global DNA methylation levels in males were significantly higher than in females (median %5mC: 1.82 vs. 1.03, males and females, respectively, ( p < .05)). Conclusion: No association was found between global DNA methylation and child cognition and behavior; however given the small sample, this study should be pooled with other cohorts in future meta‐analyses. Abstract : This study quantified the relationship between global DNA methylation and cognition and behavior at 4 years of age. Data were collected from 73 children indicated no statistically significant associations were found between global DNA methylation levels and child cognition or behavior ( p > .05). Global DNA methylation levels in males were significantly higher than in females (median %5mC: 1.82 vs. 1.03, males and females, respectively, ( p < .05)).